Comparison of strength and stability of bicycle frames made from 6061-T6 Aluminum (SS) and Commercially Pure CP-Ti UNS R50700 Grade 4 (SS) materials - Muhlisin, Iip; Feblidiyanti, Niera (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
This study examines the comparison of strength and stability between two commonly used materials in bicycle frame manufacturing, Aluminum 6061-T6 (SS) and Commercially Pure CP-Ti UNS R50700 Grade 4 (SS), through simulations using SolidWorks software. By analyzing the mechanical response of bicycle frames made from these materials under static loading conditions, the research focuses on mechanical characteristics, stress distribution, strain, safety factors, and structural stability. The results reveal significant differences in material response and structural performance between Aluminum 6061-T6 (SS) and Commercially Pure CP-Ti UNS R50700 Grade 4 (SS). These findings provide crucial insights into material selection for bicycle frame design, aiming to achieve an optimal balance between strength, elasticity, and stability. The practical significance of these findings lies in their potential applications in the bicycle industry, where understanding the strengths and limitations of different materials can lead to better-informed decisions in frame design. By optimizing material selection based on specific performance requirements, manufacturers can develop bicycle frames that cater to a wide range of uses, from high-performance sports models to durable, everyday commuting bikes. These insights serve as a foundation for further research and the development of superior bicycle frame designs, ultimately enhancing efficiency and performance in real-world applications.